The Relationship between GDP and Biomass Energy Per Capita in Sub-Saharan Africa - SEKANABO, Desire; Nyandwi, Elias; Dieu, Hakizimana Khan Jean de; Thomas, Valerie M. (International Journal of Energy Economics and Policy, 2022)
The relationship between traditional biomass energy consumption and economic growth is examined in 15 Sub-Saharan Africa countries based on available World Bank data for the period of 1990–2019, in terms of biomass energy per capita and real GDP per capita. Three sets of countries, showing different relations of GDP and biomass are discussed. On one hand, the largest set of countries shows increasing GDP and increasing biomass use per capita. On the other hand, the next largest set of countries shows increasing GDP and decreasing biomass use per capita. There is also a small set of countries with decreasing GDP, with examples of both increasing and decreasing biomass use per capita. For most of these countries we find a positive relationship between biomass energy consumption and GDP, per person. The results indicate that biomass energy use does not necessarily fall with increasing GDP, and also that several countries have introduced successful measures to reduce biomass use.